2023
DOI: 10.1021/acs.langmuir.3c00600
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Assisted Protocellular Membrane Formation with Ethanolamine-Based Amphiphiles

Abstract: Prebiotic membranes are one of the essential elements of the origin of life because they build compartments to keep genetic materials and metabolic machinery safe. Since modern cell membranes are made up of ethanolamine-based phospholipids, prebiotic membrane formation with ethanolamine-based amphiphiles and phosphates might act as a bridge between the prebiotic and contemporary eras. Here, we report the prebiotic synthesis of O-lauroyl ethanolamine (OLEA), O-lauroyl methyl ethanolamine (OLMEA), and O-lauroyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Pyrene is an extensively used chromophore to determine the CMC of surfactants and surfactant mixtures. , The concentration of the pyrene was kept at 1 μM to prevent the formation of any excimer . Pyrene exhibits five well-defined fluorescence vibronic bands at 373, 378, 384, 389, and 393 nm upon excitation at 337 nm . The fluorescence intensity ratio of band I and band III (referred to as the I 1 / I 3 ratio) is most sensitive toward the polarity of the medium. , In polar environments, the intensity of the first vibronic band ( I 1 ) at 373 nm is enhanced, whereas that of the third vibronic band ( I 3 ) at 384 nm remains unaffected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrene is an extensively used chromophore to determine the CMC of surfactants and surfactant mixtures. , The concentration of the pyrene was kept at 1 μM to prevent the formation of any excimer . Pyrene exhibits five well-defined fluorescence vibronic bands at 373, 378, 384, 389, and 393 nm upon excitation at 337 nm . The fluorescence intensity ratio of band I and band III (referred to as the I 1 / I 3 ratio) is most sensitive toward the polarity of the medium. , In polar environments, the intensity of the first vibronic band ( I 1 ) at 373 nm is enhanced, whereas that of the third vibronic band ( I 3 ) at 384 nm remains unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrene exhibits five well-defined fluorescence vibronic bands at 373, 378, 384, 389, and 393 nm upon excitation at 337 nm . The fluorescence intensity ratio of band I and band III (referred to as the I 1 / I 3 ratio) is most sensitive toward the polarity of the medium. , In polar environments, the intensity of the first vibronic band ( I 1 ) at 373 nm is enhanced, whereas that of the third vibronic band ( I 3 ) at 384 nm remains unaffected. As displayed in Figure S5a, the plot of intensity ratio ( I 1 / I 3 ) against the concentration of surfactants contains an inflection point that defines the CMC value of that surfactant in a particular medium (here, 10 mM PB).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group proposed that apart from the anionic amphiphiles, cationic amphiphiles were also important in protocell formation and catalysis. Particularly, we have shown that a lysine-based prebiotic cationic amphiphile and anionic fatty acids may work in tandem (catanionic complex formation) to form a prebiotic membrane at low CVC and assisted in regioselective peptide bond formation . The protocell forming ability of the mixture of cationic amino acid-based amphiphiles (lysine octyl ester, LysOct) and anionic fatty acid amphiphiles (decanoic acid) led to a window of opportunities to explore the capabilities of phosphate- and sulfate-based anionic amphiphiles.…”
Section: Introductionmentioning
confidence: 99%